2021
DOI: 10.1051/sicotj/2021012
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between rotator cuff integrity and acromiohumeral distance following open and arthroscopic rotator cuff repair

Abstract: Background: Acromiohumeral distance (AHD) has become both a diagnostic and prognostic parameter related to rotator cuff pathology which is always measured in a 2-dimensional plane. The purposes of this study were (1) to evaluate the regional AHD with MRI following open and arthroscopic rotator cuff repair and, (2) to investigate its association to the rotator cuff integrity following medium to large size rotator cuff repair with open and arthroscopic manner. Methods: A retrospective review of 112 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(32 reference statements)
0
3
1
Order By: Relevance
“…This is irreversible and increases in the case of tendon retear. 38 We found smaller AHD on the repaired side compared with the healthy side regardless of whether there was an intact or retorn tendon, in contrast to another study that found a significantly greater AHD, measured by MRI, in healed tears compared with retears, 25 as well as studies indicating that the retear led to superior migration of the humeral head and a reduced AHD. 54 However, comparison between 2 different imaging modalities must always be made with caution because while US is conducted with the patient in the functional upright position, standard MRI is carried out with the patient in the supine position.…”
Section: Retearcontrasting
confidence: 42%
“…This is irreversible and increases in the case of tendon retear. 38 We found smaller AHD on the repaired side compared with the healthy side regardless of whether there was an intact or retorn tendon, in contrast to another study that found a significantly greater AHD, measured by MRI, in healed tears compared with retears, 25 as well as studies indicating that the retear led to superior migration of the humeral head and a reduced AHD. 54 However, comparison between 2 different imaging modalities must always be made with caution because while US is conducted with the patient in the functional upright position, standard MRI is carried out with the patient in the supine position.…”
Section: Retearcontrasting
confidence: 42%
“…Currently, double-row surgery is generally considered superior to single-row surgery in various studies [18] . The data also indicate that compared to single-row suturing, double-row suturing has a more pronounced effect on reducing the torque values of the shoulder joint, demonstrating that double-row suturing can more effectively restore the biomechanical function of the shoulder joint [19][20][21] . However, since the choice of surgery is not solely determined by the doctor and the cost of surgical materials has consistently constituted a signi cant portion of the surgical expenses, there are still many individuals opting for the less costly single-row suturing due to nancial constraints.…”
Section: Discussionmentioning
confidence: 84%
“…Our study did not compare this measuring method for both treatments, but Kholinne et al found that a larger AHD was observed in open repair. [25][26][27] Literature on the current tendency of operating RCRs via full ART versus MO techniques has reported conflicting results. ART RCR has recently emerged as the gold standard of treatment for patients with rotator cuff tears that require surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not compare this measuring method for both treatments, but Kholinne et al found that a larger AHD was observed in open repair. [25–27]…”
Section: Discussionmentioning
confidence: 99%